Price dynamics of Swedish pharmaceuticals - JANSSEN, Aljoscha (Institutional Knowledge at Singapore Management University, 2022)
This paper investigates price patterns of off-patent pharmaceuticals in Sweden. I show that price dynamics are dependent on the number of competitors in the market. The price patterns follow predictions from a model of dynamic price competition in which the demand for pharmaceuticals incorporates the known biases of consumers: habit persistence and brand preferences. Using the regulated market of Swedish pharmaceuticals, I show that price dynamics may help in identifying possible tacit collusion by manufacturers in markets where consumers experience behavioral frictions.